A cross-section analysis of sedimentary organic matter in a mangrove ecosystem under dry climate conditions: The Somone estuary, Senegal. (January 2015) - Sakho, Issa; Mesnage, Valérie; Copard, Yoann; Deloffre, Julien; Faye, Guilgane; Lafite, Robert; Niang, Isabelle
Graphical abstract: Highlights: This paper present a biogeochemical study of the Somone mangrove, Senegal. Organic matter are autochthonous origin: ligno-cellulosic-derived OM. Both of pneumatophores and crab burrowing activities control OM degradation. Anaerobic conditions, at the mudflat and Rhizophora, aim to OM preservation. Tidal dynamic explain sediment porewater chemistry. Abstract: Mangrove sediments are an important organic matter (OM) reservoir and play a major role in the carbon cycle. Since the 1990s, these ecosystems were subjected to numerous studies, in order to quantify the sedimentary sink for organic carbon (OC) and to characterize the organic matter sources, but remain poorly studied in Western Africa. The aim of our study is to quantify the organic carbon content and to identify the OM origin stored in the Somone mangrove sediments. Studied area is characterized by a (i) dry climate conditions with a higher rate of evaporation, (ii) lack of freshwater input by river, and (iii) tide dominated system. Here, we focus on physico-chemical properties of sediments (temperature, pH and redox), sediment grain size, water content, particulate organic carbon and dissolved organic carbon from a series of 40 cm-deep cores in four tidal contexts: mudflat, Rhizophora, and Avicennia mangroves and barren area. Results show that total organic carbon (TOC) contents range between 0.34 and 3.92 wt.% and are higher in sediments from mudflat and Rhizophora mangrove than in sediments from Avicennia mangrove and barren area. Indeed, sediments stored under Avicennia is subjected to suboxic conditions initiated by roots system and crabs bioturbation; while under Rhizophora and mudflat, local anoxic conditions are prevalent as suggest the negative Eh values and the occurrence of framboidal pyrites. Mangrove sediments of the Somone estuary contain an autochthonous lignocellulosic-derived organic matter. The youngest and stunted form of the Somone mangrove explains the low organic carbon content of sediments; where dry climate conditions limit the organic matter production by the mangrove forest. The shallow depth at which the organic matter of the former mudflat was found confirms that the Somone mangrove is subjected to a low sedimentation rate. This suggests that organic carbon burial depends on others processes than sedimentation. Then, in the Somone mangrove ecosystem, both of pneumatophores and burrowing crab activities are the main factors that control OM degradation ( Avicennia station) while anaerobic conditions (mudflat and Rhizophora ) promote OM preservation.